THE CLEAN AIR ACT’S NEW SOURCE REVIEW PROGRAM: BENEFICIAL TO PUBLIC HEALTH OR MERELY A SMOKE-AND-MIRRORS SCHEME? (Utah Environmental Law Review, 2009)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} In 1970, Congress enacted the Clean Air Act (CAA), which aimed to protect public health by reducing air pollution and by maintaining safe levels of harmful emissions. In 1977, Congress amended certain provisions of the CAA to further strengthen the authority of the Environmental Protection Agency (EPA) to protect the public health from harmful air pollutants. These amendments sought to maintain acceptable levels of air quality by requiring newly constructed sources of pollution, such as electric utilities and other large emitters of pollutants, to obtain permits that would ensure compliance with national air standards. Despite the potential health benefits that could have been realized by the Clean Air Act and its 1977 New Source Review (NSR) amendments, the NSR program has led to mixed results and the public’s health has suffered as a consequence. The congressional mandate in 1970 and 1977 seemed very clear: “protect and enhance the quality of the Nation’s air resources so as to promote the public health.” With thirty years of hindsight, however, Congress’s message has been obscured greatly by corporate and political interests. The American public has been the victim of an elaborate smoke-and-mirrors scheme where public health appears to be the primary goal under the NSR program. In reality, electric utilities are emitting more than their share of dirty smoke while the federal executive branch, especially under former President George W. Bush, is providing mirrors to deflect the truth: the NSR program is failing to protect public health because of a lack of enforcement by the Environmental Protection Agency.